A modified tracheal transection approach for cervical esophageal lesion treatment: A report of 13 cases - Liu, Yang; Huang, Nan; Xu, Wei; Liu, Jie; An, Changming; Zhu, Yiming; Liu, Shaoyan; Zhang, Zongmin (Frontiers in Surgery, 2022)
Objective: Surgical interventions for tumors in the cervical esophageal region are complicated and laryngeal function is frequently sacrificed. We tried the tracheal transection approach to resect the tumor while preserving laryngeal function. Methods: Three patients with papillary thyroid cancer, six with cervical esophageal cancer (CEC), and four with CEC mixed with thoracic esophageal cancer (TEC) were enrolled. The esophagus was exposed after the trachea was transected between the second and third tracheal rings. CEC/TEC: Resection of the esophagus or/and a portion of the hypopharynx with acceptable safety margins and repair with free jejunum or tubular stomach. PTC: Suture the small esophageal incision immediately after removing the tumor. The tracheal dissection was repaired with interrupted sutures throughout the entire layer after the esophageal lesion was resected. The status of the recurrent laryngeal nerve (RLN) determined whether a tracheotomy was necessary. Results: All 13 patients had effective esophageal lesion excision, with six of them requiring intraoperative tracheotomy. Postoperative complications included a tracheoesophageal fistula (one case, 7.7%), postoperative RLN paralysis (two cases, 15.4%), and aspiration (three cases, 23.1%). Except for two patients with distant metastases, there was no recurrence in the remaining patients after 5–92 months of follow-up. Conclusion: The tracheal transection approach, as a new surgical technique, can retain laryngeal function while ensuring appropriate exposure and satisfactory surgical resection. Before surgery, the feasibility of this approach must be carefully assessed. The RLN should be protected during the procedure. The operation is both safe and effective, with a wide range of applications.